The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2008
DOI: 10.4049/jimmunol.180.9.6402
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of Blood T Cell and Antibody Reactivity to Myelin Proteins with HLA Type and Lesion Localization in Multiple Sclerosis

Abstract: Multiple sclerosis (MS) is a chronic inflammatory demyelinating disease of the CNS. The numbers of autoimmune T cells and Abs specific for proteins of CNS myelin are increased in the blood in some patients with MS. The aim of this study was to investigate whether there are correlations between the specificity of the autoimmune responses in the blood, the HLA molecules carried by the patient, and the clinical features of MS, because studies on experimental autoimmune encephalomyelitis, an animal model of MS, in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
56
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 37 publications
(59 citation statements)
references
References 42 publications
3
56
0
Order By: Relevance
“…5) (Greer et al 2008). These correlations were also observed in patients at the onset of clinical signs of disease (Greer et al 2008;Tuohy 1997) and in patients followed longitudinally over an 18-month period .…”
Section: Effects Of Hla On Sites Of Lesion Developmentsupporting
confidence: 51%
See 2 more Smart Citations
“…5) (Greer et al 2008). These correlations were also observed in patients at the onset of clinical signs of disease (Greer et al 2008;Tuohy 1997) and in patients followed longitudinally over an 18-month period .…”
Section: Effects Of Hla On Sites Of Lesion Developmentsupporting
confidence: 51%
“…This valine is also present in DRB1*15:03, which is related to development of MS in people of African ancestry, but is not present in DRB1*15:02, which is not associated with development of MS in any populations (although DRB1*15:02 can present a wide variety of other myelin peptides, suggesting that other factors besides antigenpresenting ability are involved in its lack of association with MS (Finn et al 2004). In our studies of T cell responses to PLP in MS patients, we have reported that PLP can be presented by HLA-DR4 (Greer et al 1997(Greer et al , 2008. Binding assays, however, indicate that only certain subtypes of DR4 can bind the PLP peptides strongly, e.g.…”
Section: Antigen Presentationmentioning
confidence: 85%
See 1 more Smart Citation
“…In fact, studies showed that areas of demyelination are commonly localised within previously remyelinated regions [109,110] . This inherent predisposition is likely to be determined by numerous polygenic factors, including genetic factors, such as some of the MS susceptibility factors [111] , several genes involved in the regulation of immune cell function, myelin and neural growth [112] , and genetically correlated CD4 T-cell immunoreactivity [113] .…”
Section: Relapse Phenotypementioning
confidence: 99%
“…Although many studies have tested myelin-antigen-specific Tcell responses in patients with MS, only three studies have attempted to correlate T-cell autoreactivity to one [42] or several myelin proteins [47,56] with the areas in which lesions form. One of these studies [42] investigated T-cell reactivity to PLP peptides in 10 patients with monocentric monophasic demyelinating syndromes suggestive of a first attack of MS, and another [47] compared T-cell reactivity to PLP, MBP and MOG in 10 Japanese patients with the optico-spinal form of MS and 11 patients with conventional MS.…”
Section: Is the Autoreactivity Directed Against Plp Pathogenic In Ms?mentioning
confidence: 99%